Influence of the Independence of the Board of Commissioners, the Competency of the Committee Audit, and Audit Quality on Earnings Management and its Implications on Firm Value (Empirical Study of Non-Financial State-Owned Enterprises that go Public in the - Caecilia Cahyaningsih Kristilestari; Ronny Andesto (Dinasti Publisher, 2023)
Thislresearch was conductedl with thel aim ofl obtaining evidence about the influencel of thel independence of thel board ofl commissioners, audit committeel competence and audit quality onl earnings management and the implications for firm value. Thel population ofl this studylare lnon-financial State-Owned Enterprises listed on thelIndonesia Stockl Exchange, with an observation period from l2019-2021. The sample technique used lis purposive sampling, and the analytical method as the basis for data processing is SPSS software. Thel results oflthe study found that earnings management has no effectlon firm value. The independence ofl the Boardl of Commissionersl and thel competence of the audit committeel also havel no effect onl earnings management. From this study, the only hypothesis that can be accepted is thatl audit quality hasl a significantl effect onl earnings management. Rejection of the hypothesisl can be influenced by several factors, including audit commissioners and audit committees with financial backgrounds that are only used to fulfill legal requirements. However, in practice, they need to be implemented properly or there is a conflict of interest in them